An unusual case of struma ovarii. (5th March 2021) - Koehler, Viktoria F; Keller, Patrick; Waldmann, Elisa; Schwenk, Nathalie; Kitzberger, Carolin; Schmohl, Kathrin A; Knösel, Thomas; Stief, Christian Georg; Spitzweg, Christine
Abstract : Summary: Struma ovarii is a teratoma of the ovaries predominantly composed of thyroid tissue. Hyperthyroidism associated with struma ovarii is rare, occurring in approximately 8% of cases. Due to the rarity of struma ovarii, available data are limited to case reports and small case series.We report on a 61-year-old female patient with known Hashimoto's thyroiditis on levothyroxine replacement therapy for years with transition to clinical and biochemical hyperthyroidism despite antithyroid medication with carbimazole (10 mg/day), new diagnosis of urothelial carcinoma and an adnexal mass suspicious of ovarian cancer. The patient underwent resection of the adnexal mass and histopathology revealed a mature teratoma predominantly composed of thyroid tissue showing high levels of sodium iodide symporter protein expression. Following struma ovarii resection and disappearance of autonomous production of thyroid hormones, the patient developed hypothyroidism with severely decreased thyroid hormone levels fT4 and fT3 (fT4 0.4 ng/dL, reference interval 0.9–1.7 and fT3 < 1.0 pg/mL, reference interval 2.0–4.4). This has previously been masked by continued thyroid-stimulating hormone suppression due to long-term hyperthyroidism pre-surgery indicating secondary hypothyroidism, in addition to primary hypothyroidism based on the known co-existing chronic lymphocytic thyroiditis of the orthotopic thyroid gland. Levothyroxine administration was started immediately restoring euthyroidism.This case illustrates possible diagnostic pitfalls in a patient with two concurrent causes of abnormal thyroid function. Learning points: Struma ovarii is an ovarian tumor containing either entirely or predominantly thyroid tissue and accounts for approximately 5% of all ovarian teratomas. In rare cases, both benign and malignant struma ovarii can secrete thyroid hormones, causing clinical and biochemical features of hyperthyroidism. Biochemical features of patients with struma ovarii and hyperthyroidism are similar to those of patients with primary hyperthyroidism. In such cases, thyroid scintigraphy should reveal low or absent radioiodine uptake in the thyroid gland, but the presence of radioiodine uptake in the pelvis in a whole body radioiodine scintigraphy. We give advice on possible diagnostic pitfalls in a case with two simultaneous causes of abnormal thyroid function due to the co-existence of struma ovarii.